Using Video Critics Strategy in Developing Students’ Writing - Muh Asshiddiq; Farida Abd Rauf (LETS: Journal of Linguistics and English Teaching Studies, 2022)
This study was aimed to see the writing ability development at SMA Negeri 11 Sidrap. The objective of this study is to get the empirical data of the differences between students’ score of writing test who were and were not taught by using Video Critics strategy. The population of this research consists of 56 students. The sample of the research were class XI IPS as the experimental group which consists of 17 students and XI MIPA as the control group which consists of 39 students. The research method used in this research was quasi-experimental with nonequivalent control group design. The data was collected through pretest and posttest. It aimed to know whether Video Critics strategy in teaching writing can develop students’ writing ability